An Experiment On Shariah-based Personal Financial Transactions Using A Business Game - Syahidawati Hj. Shahwan; Zurina Shafii; Supiah Salleh; Norhazlina Ibrahim; Kasumalinda Alwi; Safeza Mohd Sapian; Halizah Md. Arif (Zes Rokman Resources, 2024)
Volume: 8 Issue : 1